1986
DOI: 10.1152/ajprenal.1986.250.1.f58
|View full text |Cite
|
Sign up to set email alerts
|

PGI2 synthesis and excretion in dog kidney: evidence for renal PG compartmentalization

Abstract: To assess the concept of compartmentalization of renal prostaglandins (PG), we compared entry of PGE2 and the PGI2 metabolite 6-keto-PGF1 alpha into the renal vascular and tubular compartments, in sodium pentobarbital-anesthetized dogs. Renal arterial 6-keto-PGF1 alpha infusion increased both renal venous and urinary 6-keto-PGF1 alpha outflow. In contrast, renal arterial infusion of arachidonic acid (AA) or bradykinin (BK) increased renal venous 6-keto-PGF1 alpha outflow but had no effect on its urinary outflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…There is no evidence for tubular secretion of 6-keto-PGF1,. Stop flow experiments (Boyd et al 1986) indicate that 6-keto-PGF1, is not added to the urine beyond the glomerulus. Urinary excretion of 6-keto-PGF,, is not influenced by inhibition of the organic acid secretory pathway with probenecid (Rosenkranz et al.…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence for tubular secretion of 6-keto-PGF1,. Stop flow experiments (Boyd et al 1986) indicate that 6-keto-PGF1, is not added to the urine beyond the glomerulus. Urinary excretion of 6-keto-PGF,, is not influenced by inhibition of the organic acid secretory pathway with probenecid (Rosenkranz et al.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that cyclooxygenase plays a role in the renal vasodilatory effect of heme is reinforced by the finding that heme increases the urinary excretion of 6-keto-PGF 1␣ , the inactive derivative of PGI 2 . As PGI 2 is known to promote renal vasodilation, 17 the renal vasodilatory effect of heme is attributable to an enhanced production of renal PGI 2 . This conclusion fits well with the results of a previous study documenting that heme promotes prostaglandin production in cultured endothelial cells.…”
Section: Effects Of Intravenous Administration Of Heme In Rats Pretrementioning
confidence: 99%
“…1986). Boyd et al (1986) recently examined the compartmentalization of renal PG synthesis and excretion in vivo in canine kidneys. Their results with AA and bradykinin as agonists are in agreement with the present findings; they concluded that "in the dog PGE2 synthesized in the kidney enters directly into both the renal vascular and tubular compartments, but 6-keto-PGFI , of renal origin enters directly into only the renal vascular compartment."…”
Section: Discussionmentioning
confidence: 99%